Sicilia - Gasparini, Roberto; Panatto, Donatella; Dirodi, Bruna; Prato, Rosa; Amunni, Gianni; Turello, Valter; Sudano, Luigi; Cristoforoni, Paolo; Boccalini, Sara; Bonanni, Paolo (Farmeconomia. Health Economics and Therapeutic Pathways, 2012)
In Sicilia region 64% of women (aged 24-64) are screened regularly, meaning every 3 years. The analysis on cross-protective activity exercised by bivalent and quadrivalent vaccines shows that the bivalent vaccine could prevent more pre-cancerous lesions and cases of cervicocarcinoma than quadrivalent, and that the latter could prevent genital warts that are not prevented by bivalent. The major number of cases avoided by the bivalent make it possible to fully offset the cost savings related to warts associated with the quadrivalent vaccine. Furthermore, a cost-effectiveness analysis shows that, considering regional tariffs, the multiple cohort (12-year-old + 25-year-old women) vaccination strategy with a 90% coverage could prevent 82 cases of cervicocarcinoma and 37 related deaths more than the vaccination of only 12-year-old girls, and thus proves to be cost-effective (10,534 €/QALY).